Dersú Uzalá - Arsenʹev, V. K. 1872-1930 (Akal bolsillo, 2011)
Arseniev describes three explorations in the Ussurian taiga along the Sea of Japan above Vladivostok, beginning with his first encounter of the solitary aboriginal hunter named Dersu, a member of the Gold tribe, who thereafter becomes his guide. Each expedition is beset with hardship and danger: through blizzard and flood and assorted deprivations, these two men forge an exceptional friendship in their mutual respect for the immense grandeur of the wilderness. But the bridges across language, race and culture also have limitations, and the incursion of civilization exacts its toll. Dersu the Trapper is at once a witnessing of Russia's last frontier and a poignant memoir of rare cross-cultural understanding.